Zambia : Fifth and Sixth Reviews Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Nonobservance of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the Fifth and Sixth Reviews Under the Poverty Reduction and Growth Facility Arrangement discusses Zambia's strong macroeconomic performance and budget execution. High copper prices and extensive debt relief helped to strengthen Zambia's external position and allowed it to build up international reserves. The structural agenda will continue to focus on strengthening public expenditure management and improving debt management. Although measures have been put in place to improve expenditure management, the authorities may still face difficulties until the new treasury functions are fully in place.